Traditional uses, phytochemistry, pharmacology and toxicology of garlic (Allium sativum), a storehouse of diverse phytochemicals: A review of research from the last decade focusing on health and nutritional implications - Tudu, Champa Keeya; Dutta, Tusheema; Ghorai, Mimosa; Biswas, Protha; Samanta, Dipu; Oleksak, Patrik; Jha, Niraj Kumar; Kumar, Manoj; Radha,; Proćków, Jarosław; Pérez de la Lastra, José M.; Dey, Abhijit (Frontiers in Nutrition, 2022)
Allium sativum L. (Garlic) is a fragrant herb and tuber-derived spice that is one of the most sought-after botanicals, used as a culinary and ethnomedicine for a variety of diseases around the world. An array of pharmacological attributes such as antioxidant, hypoglycemic, anti-inflammatory, antihyperlipidemic, anticancer, antimicrobial, and hepatoprotective activities of this species have been established by previous studies. A. sativum houses many sulfur-containing phytochemical compounds such as allicin, diallyl disulfide (DADS), vinyldithiins, ajoenes (E-ajoene, Z-ajoene), diallyl trisulfide (DATS), micronutrient selenium (Se) etc. Organosulfur compounds are correlated with modulations in its antioxidant properties. The garlic compounds have also been recorded as promising immune-boosters or act as potent immunostimulants. A. sativum helps to treat cardiovascular ailments, neoplastic growth, rheumatism, diabetes, intestinal worms, flatulence, colic, dysentery, liver diseases, facial paralysis, tuberculosis, bronchitis, high blood pressure, and several other diseases. The present review aims to comprehensively enumerate the ethnobotanical and pharmacological aspects of A. sativum with notes on its phytochemistry, ethnopharmacology, toxicological aspects, and clinical studies from the retrieved literature from the last decade with notes on recent breakthroughs and bottlenecks. Future directions related to garlic research is also discussed.